The Neurophysiology of Auditory Hallucinations – A Historical and Contemporary Review - van Lutterveld, Remko; Sommer, Iris E.; Ford, Judith M. (Frontiers in Psychiatry, 2011)
Electroencephalography (EEG) and magnetoencephalography (MEG) are two techniques that distinguish themselves from other neuroimaging methodologies through their ability to directly measure brain-related activity and their high temporal resolution. A large body of research has applied these techniques to study auditory hallucinations. Across a variety of approaches, the left superior temporal cortex is consistently reported to be involved in this symptom. Moreover, there is increasing evidence that a failure in corollary discharge, i.e. a neural signal originating in frontal speech areas that indicates to sensory areas that forthcoming thought is self-generated, may underlie the experience of auditory hallucinations